A companion to nineteenth-century philosophy - Shand, John (Wiley, 2019)
Chapter 5 Historicizing Naturalism: Mill, ComteMill, Naturalism and Knowledge; The Rejection of the A Priori; Induction; The Scope of Inductive Knowledge; Worries: Circularity and Hypothesis; Mill, Comte and the History of Knowledge; Naturalism and History; Comte's Three Stage Law; Reason and History; Comte's Influence on Mill; Mill as a Historicist; Historicism; Associationism and Theory Laden Observation; Naturalism and Relativism; Realism and the World in Itself; Notes; Bibliography; Chapter 6 The Single Individual is Higher than the Universal: Kierkegaard
Includes bibliographical references and index
Includes index
Keywords: 1800-1899; Electronic books; Aufsatzsammlung; Geschichte 1800-1900; Philosophie